Legitimidade do espaço psicopedagógico no atendimento educacional especializado - Smolareck, Rodrigo Dalosto (2017)
The present study aims to theorize, based on ethnographic research, on the institutionality of psychopedagogy in the Specialized Educational Service of the Alegrete Municipal Education Network in Rio Grande do Sul State. The objective was to contribute to the implementation of inclusive actions through the construction of guidelines for psychopedagogical practice in multifunctional resource rooms. In order to achieve this, the methodological approach of the present study consisted of data collection in a qualitative dimension while meeting the complexity of the culture of the research context. Content analysis was validated and the data examined by the need to perceive, legitimately, the necessary informational demands to categorize this academic production into systematization. The research proposal turned to the Special Education Specialists, who work in the Specialized Educational Service – SES, with specialization in psychopedagogy in order to bring the contributions of these professionals to the field of inclusive education. In short, the research concluded how psychopedagogical practice with regard to students with special educational needs can be established in an organizational context, since the psychopedagogue is inserted into Specialized Educational Service as a Special Education Specialist. The final product, which was a result of the study, was named Protocol Guidelines for Psychopedagogical Practice in SES, therefore constituting a promising field of practice in the field of research.